Dynamics Of Environmental Factors In Relation To Phytoplankton Species In A Pond Of Old Dhaka, Bangladesh - Jerin, Sahajadi; Gani, Md Ataul; fasane, Md Almujaddade Al; Khondker, Moniruzzaman (Journal of the Asiatic Society of Bangladesh, Science, 2016)
The relationship between different environmental factors and abundance of phytoplankton species was studied for one year in a pond of old Dhaka named Sikkatuli pond. The range of annual mean of different variables in the pond was air and water temperatures 20 - 31.75˚C, secchi depth 21 - 54 cm, pH 7.39 - 8.3, alkalinity 3.9 - 9.2 meq/l, conductivity 484.5 - 2273.34 μS/cm, DO 3.35 - 8.33 mg/l, TDS 224.67 - 380.5 mg/l, SRS 12.03 - 79.93 mg/l, NO3-N 0.18 - 0.435 mg/l, SRP 0.33 – 4.28 μg/l, chlorophyll a 196.08 - 362.76 μg/l and phaeopigment 30.51 - 212.2 μg/l. During the investigation Cryptomonas erosa var. reflexa, Rhodomonas lens, Cyclotella comensis, Merismopedia gluaca, Euglena acus, Lyngbya limnetica, Chlorella vulgaris, Arthrospira platensis, Trachelomonas volvocina, Oscillatoria agardhii, Synechocystis aquatilis, Pelonema aphane and Peridinium sp. were found to be dominant phytoplankton. Pearson correlation showed that only alkalinity correlated with phytoplankton at 5% significant level. RDA orientation showed that air temperature, water temperature, secchi depth, chl a and pheopigment concentration are the important environmental factors. RDA ordination plot also showed that phytoplankton species of Pelonema aphane and Peridinium sp. were negatively correlated with secchi depth. Negative correlation was also observed between Trachelomonas volvocina and water temperature. Asiat. Soc. Bangladesh, Sci. 42(2): 169-175, December 2016